Epidemiology of injuries in tennis - Kenn, M. (1997)
A study of 242 players was performed in 1996 to assess the distribution of injuries in local tournament players compared with recreational players. Retrospective injury registration over the last 13.4 years (mean) showed 496 injuries, 53% affecting the lower extremities, 39% the upper extremities, 2.2% head injuries and 5.8% injuries of the spinal column. Men were injured more frequently than women, and tournament players more often that recreational players. Among tournament players aged 18-25, 54% of injuries were ankle lesions and 24% knee injuries. In tournament players aged over 25, angle injuries decreased to 40% but knee injuries increased to 30%. A correlation was found between equipment and preferred playing style in the mechanics of injuries. Players using air shoes had significantly fewer knee injuries (p<5%). Players who preferred to serve and volley had significantly more wrist injuries (p<5%) than those focusing on baseline play.